Effectiveness of Mindfulness-Based Intervention (MBI) on Reducing Work Stress - Auliya Diah Safitri; Ananta Yudiarso (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Workplace stress is the result of an individual's interaction with their job tasks, which can create tension and imbalance both physically and psychologically. This impacts emotions, cognitive abilities, and the mental state of an employee. This study was conducted to determine the effectiveness of Mindfulness-Based Intervention in reducing workplace stress through a meta-analysis method by reviewing relevant literature from 10 international research journals related to the study variables. The total number of participants in this study was 1,119 individuals divided into two groups: the experimental group (n=560) and the control group (n=559). Based on statistical calculations using mean (M), standard deviation (SD), and the number of participants (n), the effect size value obtained from a random-effect model was determined. Thus, it was sought to establish whether Mindfulness-Based Intervention is an effective treatment for reducing workplace stress and to what extent this effectiveness is. The research results indicated a random effect model value of -0.536 (95% CI = (-0.8208 to -0.2506). The p-value was found to be <0.001 with an inconsistency value (I^2) of 80.6%. Based on the results of the meta-analysis, it can be concluded that Mindfulness-Based Intervention has a medium effect on workplace stress. This suggests that Mindfulness-Based Intervention is less successful in reducing workplace stress and would be more effective if used in conjunction with other types/methods of intervention.Stres kerja adalah hasil dari interaksi individu dengan tugas pekerjaannya, yang bisa menciptakan ketegangan dan ketidakseimbangan baik secara fisik maupun psikologis. Hal ini berdampak pada emosi, kemampuan berpikir, serta kondisi mental seorang pekerja. Penelitian ini dilakukan untuk mengetahui efektifitas Mindfulness Based Intervention untuk menurunkan stres kerja dengan menggunakan metode meta-analisis melalui reviu literatur dari 10 jurnal penelitian international yang relevan dengan variabel penelitian. Jumlah partisipan pada penelitian ini 1.119 orang yang dibagi dalam dua kelompok yakni kelompok eksperimen (n=560 orang) dan kelompok kontrol (n=559 orang). Berdasarkan perhitungan statistik dengan menggunakan data mean (M), standar deviasi (SD), dan jumlah partisipan (n) akan menemukan nilai effect size yang diperoleh dari random effect. Dengan demikian, nantinya akan ditemukan bahwa apakah Mindfulness Based Intervention merupakan treatment yang memiliki efektifitas untuk menurunkan stres kerja dan seberapa besar nilai efektifitas yang diberikan. Hasil Penelitian menunjukkan nilai random effect model yaitu sebesar -0,536 (95% CI = (-0,8208 sampai -0,2506). Hasil dari nilai p Value = <0.001 dengan nilai inkonsitensi (I^2) = 80,6 %. Berdasarkan hasil uji meta analisis dapat disimpulkan mindfulness-based intervention memiliki efek medium terhadap stres kerja. Hal ini menunjukkan bahwa, mindfulness-based intervention kurang berhasil dalam menurunkan stres kerja, sehingga akan lebih efektif jika salah satu jenis/ metode intervensi digunakan bersamaan dengan intervensi lain.